Repurposing bromocriptine for Aβ metabolism in Alzheimer’s disease (REBRAnD) study: randomised placebo-controlled double-blind comparative trial and open-label extension trial to investigate the safety and efficacy of bromocriptine in Alzheimer’s disease with presenilin 1 (PSEN1) mutations - Hidekazu Tomimoto; Takayuki Kondo; Yoshihide Sunada; Hidehiro Ishikawa; Akihiro Shindo; Yuishin Izumi; Haruhiko Banno; Ryuji Uozumi; Satoshi Morita; Koji Fujita; Ryosuke Takahashi; Haruhisa Inoue; et al. (BMJ Open, 2021)
Introduction Alzheimer’s disease (AD) is one of the most common causes of dementia. Pathogenic variants in the presenilin 1 (PSEN1) gene are the most frequent cause of early-onset AD. Medications for patients with AD bearing PSEN1 mutation (PSEN1-AD) are limited to symptomatic therapies and no established radical treatments are available. Induced pluripotent stem cell (iPSC)-based drug repurposing identified bromocriptine as a therapeutic candidate for PSEN1-AD. In this study, we used an enrichment strategy with iPSCs to select the study population, and we will investigate the safety and efficacy of an orally administered dose of bromocriptine in patients with PSEN1-AD.Methods and analysis This is a multicentre, randomised, placebo-controlled trial. AD patients with PSEN1 mutations and a Mini Mental State Examination-Japanese score of ≤25 will be randomly assigned, at a 2:1 ratio, to the trial drug or placebo group (≥4 patients in TW-012R and ≥2 patients in placebo). This clinical trial consists of a screening period, double-blind phase (9 months) and extension phase (3 months). The double-blind phase for evaluating the efficacy and safety is composed of the low-dose maintenance period (10 mg/day), high-dose maintenance period (22.5 mg/day) and tapering period of the trial drug. Additionally, there is an open-labelled active drug extension period for evaluating long-term safety. Primary outcomes are safety and efficacy in cognitive and psychological function. Also, exploratory investigations for the efficacy of bromocriptine by neurological scores and biomarkers will be conducted.Ethics and dissemination The proposed trial is conducted according to the Declaration of Helsinki, and was approved by the Institutional Review Board (K070). The study results are expected to be disseminated at international or national conferences and published in international journals following the peer-review process.Trial registration number jRCT2041200008, NCT04413344.